Liquefaction Potential Post-Earthquake in Yogyakarta - AGUS SETYO MUNTOHAR, S.P.R. WARDANI (SEAGS, 2010)
A 6.3 Mw earthquake on May 27, 2006 shook the provinces of Yogyakarta, number of seismic damages were reported. The damages were identified because of liquefaction phenomena during the ground vibration. The Universitas Muhammadiyah Yogyakarta (UMY) campus was constructed on 28 hectare which mostly rested on a sand deposit layer and the ground water table was shallow relatively. Theoretically, the site was susceptible to liquefaction during ground-shaking. Reconnaissance study after the earthquake was found some sand boiling sites near at the UMY area. This paper addresses two major objectives that is to evaluate the possible ground acceleration and liquefaction probability at UMY campus after the earthquake. Liquefaction potential was analyzed based on the SPT-N data from six boreholes. The probability of liquefaction was also investigated with the depth from ground surface. Three different peak ground accelerations, i.e. 0.14g, 0.25g, and 0.49g, were evaluated in this study. The results show that liquefaction triggered at very shallow depth in area near BH1, BH2, and BH4. Area surround BH3, BH5, and BH6 were susceptible to liquefaction at a depth below 20 m from ground surface. In general, liquefaction occurred with probability ranging from 5% to 90%.